EVALUATION OF SCHOOL LITERACY MOVEMENT PROGRAM FOR STUDENTS AND TEACHERS - Suherman SUHERMAN (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2021)
This research is motivated by the low reading interest in the society of Indonesia and the movement of school literacy program launched by the goverment to enhance students ability to think critically, analysis, be creative and innovative through various activities including: reading, seeing, listening, writing and speaking. The research was conduced at MIN 4 Jakarta Selatan because MIN 4 South Jakarta was one of the madrasah that have implemented the school literacy movement program. The purpose of this research is to know the evaluation of movement of school literacy program in madrasah, obstacles and feedback related to evaluation of movement of school literacy program. This research uses evaluation method of CIPP(Conteks, Input, Process, Product) in analyzing the movement of school literacy program. Respondents from this study are students and teachers who are willing to fill in google form which contains questionnaires related to the implementation of movement of school literacy. The results of the evaluation indicate that 83% said that the leaners like to read and program the movement of school literacy program has been implemented in the madrasah is in accordance with the national objectives.